Enhancing Rosemary (Rosmarinus officinalis, L.) Growth and Volatile Oil Constituents Grown under Soil Salinity Stress by Some Amino Acids - Ahmad H. Al-Fraihat; Sati Y. Al-Dalain; Ahmad A. Zatimeh; Moawiya A. Haddad (Horticulturae, 2023)
The current study was carried out during the two consecutive winter seasons of 2019/2020 and 2020/2021 at the Experimental Farm of Ash-Shoubak University College, Jordan, as a pot experiment. This experiment was planned to evaluate the impact of various soil salinity levels (1.17, 3.34, 6.51, and 9.68 ds/m) and amino acid types (control, L-tryptophan acid at 100 ppm, glutamine acid at 200 ppm, and L-tryptophan acid + glutamine acid) as well as their combinations on growth, salt resistance index, and some of the chemical constituents of rosemary plants. The obtained results indicated that plant height and the total herb dry weight of rosemary, the salt resistance index (SRI), and the total chlorophyll in leaves were discernably reduced with increasing soil salinity levels compared with the control. However, salinity enhanced leaf proline content. Each amino acid or its mixture improved plant growth, chlorophyll content, and SRI parameters. The SRI percentage of R. officinalis enhanced to more than 100% under a soil salinity level of 1.17 ds/m, combined with amino acids at any type, when compared with the other combination treatments. Furthermore, GC/MS showed that the identified compounds ranged from 98.39% to 99.18% and the unidentified compounds from 0.82% to 1.61% from the volatile oil of rosemary plants. The major constituents of volatile oil samples were camphor (34.95% to 40.21%), D-verbenone (13.74% to 15.23%), and α-pinene (13.21% to 16.73%).